Carbonation curing of mortars produced with reactivated cementitious materials for CO2 sequestration. (10th January 2023) - Li, Ye; Han, Dongsheng; Wang, Haodong; Lyu, Hanxiong; Zou, Dujian; liu, Tiejun
Abstract: Low-carbon emission mortar samples were prepared using reactivated cementitious materials (RCMs) produced by calcinating hydrated cement paste with adjusted Ca/Si ratios. Carbonation curing was employed to enhance the cementing capacity of the RCMs and to sequestrate CO2 . The compressive strength, phase assemblage, microstructure, and environmental impacts of the mortars were analyzed. According to the results, the mortar sample produced with the RCM with a 10% addition of silica fume during calcination attained the highest compressive strength (35.3 MPa) after water curing, while higher silica contents were unfavorable because the low-lime calcium silicates that formed have limited water reactivity. Carbonation curing significantly promoted reactions of the RCMs and, thus, the compressive strength of the mortars compared to water curing. The amorphous and metastable calcium carbonates contributed more to the densification of the microstructure than the calcite. From the life cycle assessment, the RCM mortars had a significantly lower impact on global warming potential compared to Portland cement mortars. Graphical abstract: Image 1